Exploring Algorithmic Bias in Cosmopolis - Panta, Sudil (NPRC Journal of Multidisciplinary Research, 2025)
Background: Cosmopolis by Don DeLillo illustrates algorithmic bias through the protagonist’s overdependence on the data-driven financial system. Within the scope of Cosmopolis, DeLillo sketches the world as an information-driven environment, where systems of the algorithm dictate financial and social realities. This paper investigates the representation of algorithmic bias—a critical issue for contemporary AI ethics—with respect to the novel.Methods: This paper explores an algorithmic bias through critical posthumanism, political ecology, and Jean Baudrillard’s hyperreality. It describes the device through which the character Eric Packer detaches himself from the material world and the marginalization of the character Benno Levin.Results & Conclusion: The novel made clear that algorithmic bias is not a technical issue but a systemic flaw; rooted in abstract data, which mostly supersedes human reality. Packer's downfall thus reveals the hubris underlying the inherent limits of data-driven prediction, while Levin's situation points to the human cost of concerned systems. Cosmopolis is ultimately a kind of parable or cautionary tale about the urgency of transparency, ethical accountability, and the reinstatement of human agency in a world overwhelmingly driven by machines.Novelty: This study explores the algorithmic bias through the study of major protagonists like Eric Packer and Benno Levin. It investigates the structural issue of algorithmic bias by using critical posthumanism, Baudrillard’s hyperreality, and political ecology. This paper considers Cosmopolis as a foresighted critique of data-driven culture, bringing to light the "black box" dilemma and the human consequences of algorithmic marginalization before these topics were discussed in the general ethical community.